2005
DOI: 10.1101/sqb.2005.70.038
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Cancer Complexities in Genetically Engineered Mice

Abstract: Because the pRb pathway is disrupted in most solid human cancers, we have generated genetically engineered mouse cancer models by inactivating pRb function in several cell types, including astrocytes and mammary, prostate, ovarian, and brain choroid plexus epithelia. In every case, proliferation and apoptosis are acutely induced, predisposing to malignancy. Cell type dictates the pathways involved in tumor progression. In the astrocytoma model, we developed strategies to induce events in the adult brain, eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…stomach adenocarcinoma 13.3% in males and 14.3% in females; Table 3 and Figure 9), low grade lesions present in most organs indicated that RB-TS inactivation was sufficient to initiate but not to progress disease. This is consistent with our previous results in mammary [27], prostate [26], choroid plexus [29] and ovarian epithelium [28], and brain astrocytes [30], [31]. Similar to TgK19GT 121 ; β-actin Cre mice, renal hydronephrosis was also observed in 75% of males and 40% of females of induced TgK19GT 121 ;K19CreER mice at 9–16 months post induction (Table 2).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…stomach adenocarcinoma 13.3% in males and 14.3% in females; Table 3 and Figure 9), low grade lesions present in most organs indicated that RB-TS inactivation was sufficient to initiate but not to progress disease. This is consistent with our previous results in mammary [27], prostate [26], choroid plexus [29] and ovarian epithelium [28], and brain astrocytes [30], [31]. Similar to TgK19GT 121 ; β-actin Cre mice, renal hydronephrosis was also observed in 75% of males and 40% of females of induced TgK19GT 121 ;K19CreER mice at 9–16 months post induction (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…T 121 is derived from the N-terminal 121 amino acids of Simian Virus 40 (SV40) large T antigen, which evolved to inactivate the RB-mediated cell cycle brake. When directed by tissue specific promoters in transgenic mice, T 121 is sufficient to initiate tumorigenesis in prostate [26], mammary [27], ovarian [28] and choroid plexus [29] epithelial cells, as well as in central nervous system astrocytes [30], [31]. The initiation phenotype is dependent on the T 121 RB/p107/p130 binding site as demonstrated by point mutagenesis [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excellent demonstration of this approach has been applied to a set of tumor suppressor and oncogenes to delineate the tumorigenic processes that they affect. 49 Cell-specific pRb (retinoblastoma protein) inactivation was introduced by a truncated SV40 T antigen transgene whose product inactivates pRb. When combined with inactivations of Pten , p53 , and E2f1 and transgenic Kras activation in astrocytes, prostate, breast, brain, and ovarian cells, a variety of progression pathways for tumorigenesis in each of these cell types was delineated.…”
Section: Engineering Genetic Complexity Into Mouse Models Of Human Camentioning
confidence: 99%
“…p53 ϩ/Ϫ mice in C57BL/6J background (23) and Cry1 ϩ/Ϫ Cry2 ϩ/Ϫ mice with the same background (15) were used to obtain p53 Ϫ/Ϫ mice, mice with p53 Ϫ/Ϫ and single Cry, and the triple knockout mice. Most of triple knockouts were generated from crossing p53 Ϫ/Ϫ Cry1 ϩ/Ϫ Cry2 ϩ/Ϫ males and p53 ϩ/Ϫ Cry1 ϩ/Ϫ Cry2 ϩ/Ϫ females.…”
Section: Methodsmentioning
confidence: 99%